Conditionings of population exposure to electromagnetic fields associated with the rational use of 5G radiocommunication networks in Poland - Paweł Bieńkowski; Marek Zmyślony; Jolanta Karpowicz; Piotr Politański; Alicja Bortkiewicz; Jarosław Kieliszek; Konrad Rydzyński (Nofer Institute of Occupational Medicine, 2020)
In 2017, preparations were made in Poland to provide all citizens with access to the Internet at a speed of at least 30 Mb/s, and at a speed of at least 100 Mb/s for 50% of households. This goal is to be realized, among others, by means of the fifth generation (5G) radio-communication networks. This work presents the assumptions of the 5G network structure and estimates of the level of population exposure toelectromagnetic fields related to their rational use. It was also analyzed whether, from the technical point of view, 5G networks could be implemented while respecting the currently acceptable level of electromagnetic field intensity in Poland (7 V/m), taking into account the current environmental exposure caused by antennas of cellular base stations. This is a contribution to the ongoing discussion on the need to change the requirements in Poland in order to limit the level of population exposure to electromagnetic fields. Based on the available documentation of the proposed technical standards, the theoretical analysis of environmental exposure to the electromagnetic field emitted by 5G systems shows that, with rational power management, obtaining the expected (compatible with 5G standards) quality of connections via base stations installed outside of buildings and using intelligent antenna systems with controlled beams, it will be possible to maintain the electric field strength and power density below the current limit values in places accessible to the public (<7 V/m, <0.1 W/m 2 ). Med Pr. 2020;71(2):245-53